Directive Speech Acts in The Nussa Series and Their Relation to The Profile of Pancasila Students - Nurfitasari, Dwi; Wahyudi, Agus Budi (Universitas Muhammadiyah Surakarta, 2023)
This research aims to analyze directive speech acts in the Nussa series and their relationship to the profile of Pancasila students. The research method used in this research is a qualitative descriptive method. The object of this research is the speech of the character Nussa. The subject of this research is Nussa's dialogue with several figures. The data collection technique in this research is note-taking. The data validation technique in this research uses triangulation techniques. The results found in this research were 1) a total of 20 directive speech acts which were grouped into six types, namely, 2 directive speech acts of asking; 6 interrogative directive speech acts; 4 directive command speech acts; 1 prohibitive directive speech act; 2 permission directive speech acts; and 5 directive speech acts in the form of advice. 2) The directive speech act is linked to the dimensions of the Pancasila student including having faith and being devoted to God Almighty; global diversity; mutual cooperation; independence; creativity; and critical reasoning. It is hoped that educators will realize these six dimensions during learning so that they do not only focus on one or two dimensions.